Time-resolved Z-scan and thermal lens measurements in Er+3 and Nd+3 doped fluoroindate glasses - Catunda, T.; Baesso, M. L.; Messaddeq, Younes [UNESP]; Aegerter, M. A. (Elsevier, 1997)
In rare earth ion doped solids, a resonant non-linear refractive index, n2, appears when the laser pumps one of the ion excited states and the refractive index change is proportional to the excited state population. In these solids there are usually thermal and non-thermal lensing effects, where the non-thermal one is due to the polarizability difference, Δα, between excited and ground states of the ions. We have used the time resolved Z-scan and a mode-mismatched thermal lens technique with an Ar+ ion laser in Er+3 (20ZnF2-20SrF2-2NaF-16BaF2-6GaF3-(36 - x)InF3-xErF3, with x= 1, 2, 3 and 4 mol%) and Nd+3 (20SrF2-16BaF2-20ZnF2-2GdF3-2NaF-(40 - x)InF3-xNdF3, with x = 0.1, 0.25, 0.5-1 mol%) doped fluoroindate glasses. In both samples we found that the non-linear refraction is due to the thermal effect, while the non-thermal effect is negligible. This result indicates that in fluoride glasses Δα is very small (less than 10-26 cm3). We also measured the imaginary part of the non-linear refractive index (n″2) due to absorption saturation.
Keywords: Doping (additives); Electron energy levels; Ions; Pumping (laser); Refractive index; Saturation (materials composition); Scanning; Solid state lasers; Thermal effects; Thermal variables measurement; Argon ion laser; Fluoroindate glasses; Non-thermal lensing effect; Polarizability difference; Thermal lens measurements; Thermal lensing effect; Optical glass